Colorectal Cancer in Ukraine: Regional Disparities and National Trends in Incidence, Management, and Mortality - Nelya Melnitchouk; Galyna Shabat; Pamela Lu; Heather Lyu; Rebecca Scully; Krystle Leung; Molly Jarman; Andrey Lukashenko; Olena O. Kolesnik; Joel Goldberg; Jennifer S. Davids; Ronald Bleday (Journal of Global Oncology, 2018)
Purpose: The incidence of colorectal cancer (CRC) is increasing worldwide, and the greatest increase is in low- to middle-income countries, such as Ukraine. Better knowledge of epidemiology of CRC in Ukraine is needed to understand how best to decrease the burden of disease. Methods: The National Cancer Registry of Ukraine (NCRU) was queried for CRC incidence, mortality, stage, and treatment in Ukraine and assessed for regional variation from 1999 to 2015. Joinpoint analysis was used to analyze the trends. Results: The incidence of colon cancer increased from 10.6 to 13.3 occurrences per 100,000, which provided an average annual percent change (AAPC) of 1.48 (95% CI, 1.3 to 1.7; P < .05). The incidence of rectal and anal cancers also increased from 9.9 to 11.5 occurrences per 100,000, which provided an AAPC of 1.0 (95% CI, 0.8 to 1.3; P < .05). Mortality remained the same (AAPC, 0.1; 95% CI, −0.3 to 0.2; P = .4). The proportion of patients who received cancer-specific treatment increased from 54.6% to 68.5% for colon cancer and from 61% to 74.4% for rectal and anal cancers. Overall, 34.5% of patients with colon cancer and 27.5% of patients with rectal cancer died within a year of diagnosis in 2015. Great regional variations in 1-year mortality and treatment received were identified. Conclusion: The incidence of CRC in Ukraine is increasing. Despite stable mortality rates, many do not receive cancer-specific treatment, and a large proportion of patients die within a year of diagnosis. These findings illustrate the need to promote establishment of a screening program and to improve access to cancer-specific therapy in Ukraine.